Development of Dust Flea Leaf Sucking Pests (Bemisia Tabaci) and The Incidence of Viral Diseases in Sweet Potato Plants in Two Agroecosystems - Firda Widya Sari; M. Sarjan; Aluh Nikmatullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Whitefly pests (Bemisia tabaci) are leaf-sucking pests that act as vectors for the spread of viral diseases in sweet potato plants. Differences in agroecosystem conditions are suspected to affect pest populations and the development of viral diseases. This study aims to (1) identify and compare whitefly pest populations on sweet potato plants in two agroecosystems, (2) identify and compare viral disease incidence in two agroecosystems, and (3) analyze the relationship between temperature and humidity on whitefly populations and viral disease incidence. The research was carried out in drylands and technical irrigated lands by observing whitefly populations, viral disease symptoms, percentage of disease incidence, and environmental factors such as temperature and humidity. The data were analyzed using a t-test at a real level of 5% and simple linear regression. The results showed that whitefly populations and the percentage of viral disease incidence differed significantly between the two agroecosystems, with higher values on drylands than on technical irrigated land. In dry land, diseases caused by Sweet potato chlorotic stunt virus (SPCSV) and Sweet potato feathery mottle virus (SPFMV) were found, while in technical irrigation land diseases were found caused by Sweet potato virus disease (SPVD). Regression analysis showed that temperature was positively correlated, while humidity was negatively correlated with whitefly populations and viral disease incidence, with a stronger relationship in dry land than in technical irrigated land. The results of the study show that differences in agroecosystem characteristics affect the dynamics of whitefly populations and the development of viral diseases in sweet potato plants.